EFFECTIVENESS OF VIDEO TUTORIALS IN IMPROVING STUDENTS' UNDERSTANDING IN INFORMATICS LEARNING AT SENIOR HIGH SCHOOL 1 PAGARAN TAPAH DARUSSALAM - Zainul Arifin; Sri Wahyudi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to test the effectiveness of video tutorials in improving students' understanding of Informatics learning at SMA N 1 Pagaran Tapah Darussalam. This study uses a Quasi-Experimental method with a Pretest-Posttest control group design, the results of the study showed that the experimental class using video tutorials experienced a significant increase in learning outcomes with an N-gain value of 0.74 (high category), compared to the control class with the lecture method which obtained an N-Gain of 0.43 (moderate category). Observations showed that the implementation of learning was very good with an average of 92.06%, and students' responses to video tutorials were also positive with good assessments. In conclusion, video tutorials have proven to be more effective in improving students' understanding, providing learning flexibility, and increasing student involvement, so it is recommended to be applied in Informatics learning.